Pengaruh Pola Asuh Orang Tua Dan Pemanfaatan Sumber Belajar Terhadap Motivasi Belajar Siswa Kelas V Di Mi Sudirman Munggur - Malik, Abdul; Hartini, Dra. Hj. Sri Hartini, M.Pd (2017)
This study aims to: (1) To determine the influence of parenting parents on the students motivation munggur V in MI Sudirman. (2) To investigate the effect of use of learning resources to motivate students of class V in MI Sudirman munggur. (3) To determine the effect of parenting parents and use of learning resources to motivate students of class V in MI Sudirman Munggur.Populasi in this study were students of class V. This research type is quantitative. The samples used were fifth grade students academic year 2016/2017, amounting to 44 students. Data collection techniques such as questionnaires, interviews, and documentation. The analysis technique used is a simple linear regression techniques, t test, F test, and the test of determination. Based on the results showed a significant positive effect of parenting parents to motivate students of class V MI Sudirman munggur. It is based on results of multiple linear regressions parenting parents (b1) obtained t> t table, namely 2.602> 2.021 and the significance value <0.05, which is a significant positive 0,013.Pengaruh use of learning resources to motivate students of class V in MI Sudirman Munggur. It is based on results of multiple linear regressions parenting parents (b1) obtained t> t table, namely 4.836> 2.021 and the significance value <0.05, ie 0,000. "The influence of parents 'parenting and use of learning resources to students' learning motivation of students class V in MI Sudirman munggur ". It is based on the results known that that the value of F count> F table, ie 23.397> 3.23 and a significance value <0.05, ie 0,000. This means that the patterns of parenting and use of learning resources together positive and significant impact on motivation to learn. The result of the coefficient of determination (R2) obtained by 0.510 the meaning of this coefficient is that the influence exerted by the combination of variable patterns of parenting and use of learning resources on motivation to learn is by 51.0% while 49.0% are influenced by other variables.